Textbook of medical oncology - Cavalli, Francesco (Informa Healthcare, 2009)
Preface Section A: General Principles 1. Molecular biology of cancer 2. Principles of systemic therapy 3. Principles and examples of systemic molecular targeted therapies 4. Principles of clinical trials Section B: Disease-specific part 5. Breast Cancer 6. Gynaecologic cancer 7. Head and Neck Cancer 8. Primary malignant tumors of the lung and pleura 9. Gastrointestinal cancer 10. Cancers of the genito-urinary tract 11. Sarcomas 12. Leukaemias 13. Lymphoma and multiple myeloma - non Hodgkin's lymphoma 14. Lymphoma and multiple myeloma - Hodgkin Lymphoma 15. Lymphoma and multiple myeloma - multi.